Design and calculation of heat transfer of the passive cooling modules for low-pressure hydrogen vessels - Lázár, Marián; Duda, Filip; Kmeťová, Ľubomíra; Jasminská, Natália; Hudák, Šimon (International Journal for Innovation Education and Research, 2021)
This paper deals with the issue of improving the temperature management of a metal hydride tank to reduce the energy intensity of cooling. The problem of absorption and adsorption of hydrogen gas in metals, cooling of metal hydride tanks in the process of hydrogen absorption while protecting the current level of development of science and research for this area is analysed. The work also deals with numerical and experimental verification of a prototype metal hydride tank with passive cooling.